Strategi Kampanye Media Sosial dalam Membangun Gaya Hidup Bersepeda di Kalangan Anak Muda Kota Bandung - Jamal Hendrawan; Inko Sakti Dewanto (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2026)
Cycling is an activity that is currently gaining traction as part of the urban lifestyle, particularly among urban youth. Bandung, as one of Indonesia’s major cities, faces various challenges such as traffic congestion and air pollution, which continue to rise. The presence of a cycling culture is seen as a potential alternative solution that not only benefits public health but also contributes to the sustainability of the urban environment. However, young people’s interest in cycling remains inconsistent due to various factors such as a lack of supporting infrastructure, insufficient public awareness, and the dominance of motorized vehicle use. This study aims to examine social media campaign strategies for fostering a cycling lifestyle among young people in the city of Bandung through a Visual Communication Design approach. The research method employed is a qualitative approach using literature review and observation of urban cycling culture phenomena. This study utilizes the Design Thinking approach, which consists of the empathize, define, ideate, prototype, and test stages. The results indicate that social media plays a significant role in shaping young people’s perceptions and interest in cycling culture. The use of visually appealing strategies, a lifestyle-oriented approach, and content relevant to urban culture can increase audience engagement and establish cycling as a modern lifestyle